Preparation of Si doped molecularly imprinted TiO2 photocatalyst and its degradation to antibiotic wastewater. Issue 168 (2nd January 2016) - Guo, Jifeng; Li, Simeng; Duan, Liang; Guo, Ping; Li, Xiaojie; Cui, Qianqian; Wang, Hui; Jiang, Qian
ABSTRACT: TiO2, molecularly imprinted TiO2 (TiO2 /OTC) and a novel Si doped molecularly imprinted TiO2 (TiO2 /SiO2 /OTC) nano photocatalytic materials were prepared by liquid phase deposition method. The products were characterized by XRD and SEM. The photocatalytic activities of the samples were evaluated by the photocatalytic degradation of oxytetracycline wastewater under a xenon lamp irradiation. The results showed that TiO2 /SiO2 /OTC and TiO2 /OTC could improve both the photocatalytic activity and the molecular recognition ability, while the photocatalytic activities of TiO2 /SiO2 /OTC sample was more effective than TiO2 /OTC sample with 5 times reuse. The photocatalytic activity of TiO2 /SiO2 /OTC photocatalyst sample had a greater improvement and its photocatalytic degradation of oxytetracycline wastewater reached 80.79% in 120 minute reaction.